Changing patterns in the epidemiology of β‐thalassemia. (21st September 2020) - Kattamis, Antonis; Forni, Gian Luca; Aydinok, Yesim; Viprakasit, Vip
Abstract: β‐thalassemia major is an inherited hemoglobinopathy that requires lifelong red blood cell transfusions and iron chelation therapy to prevent complications due to iron overload. Traditionally, β‐thalassemia has been more common in certain regions of the world such as the Mediterranean, Middle East, and Southeast Asia. However, the prevalence of β‐thalassemia is increasing in other regions, including Northern Europe and North America, primarily due to migration. This review summarizes the available data on the changing incidence and prevalence of β‐thalassemia as well as factors influencing disease frequency. The data suggest that the epidemiology of β‐thalassemia is changing: Migration has increased the prevalence of the disease in regions traditionally believed to have a low prevalence, while, at the same time, prevention and screening programs in endemic regions have reduced the number of affected individuals. Various approaches to prevention and screening have been used. Region‐specific prevention and treatment programs, customized to align with local healthcare resources and cultural values, have been effective in identifying patients and carriers and providing information and care. Significant challenges remain in universally implementing these programs.